Recent advances in two-dimensional nanomaterials for sustainable wearable electronic devices - Jing Hu; Mingdong Dong (Journal of Nanobiotechnology, 2024)
Abstract The widespread adoption of smart terminals has significantly boosted the market potential for wearable electronic devices. Two-dimensional (2D) nanomaterials show great promise for flexible, wearable electronics of next-generation electronic materials and have potential in energy, optoelectronics, and electronics. First, this review focuses on the importance of functionalization/defects in 2D nanomaterials, a discussion of different kinds of 2D materials for wearable devices, and the overall structure–property relationship of 2D materials. Then, in this comprehensive review, we delve into the burgeoning realm of emerging applications for 2D nanomaterial-based flexible wearable electronics, spanning diverse domains such as energy, medical health, and displays. A meticulous exploration is presented, elucidating the intricate processes involved in tailoring material properties for specific applications. Each research direction is dissected, offering insightful perspectives and dialectical evaluations that illuminate future trajectories and inspire fruitful investigations in this rapidly evolving field. Graphical Abstract